Reliability and stability of Bioelectronic Medicine: a critical and pedagogical perspective - Massimo Mariello (Bioelectronic Medicine)
Abstract Bioelectronic Medicine relies on wearable or implantable electronic devices interfacing with the nervous system and other active tissues, offering innovative therapeutic solutions. However, the long-term reliability and stability of these devices remain critical challenges that must be addressed for widespread clinical adoption. Advances in materials science, device engineering, power management, and biocompatibility are essential to ensure sustained functionality in dynamic biological environments. This perspective highlights key factors affecting the durability, reliability and stability of Bioelectronic Medicine technologies, explores current solutions and emerging approaches, and outlines the necessary steps to achieve robust, long-lasting bioelectronic therapeutics. The personal view expressed in this article is aimed to provide structured, accessible insights that support teaching and learning, and is envisioned to help motivate other investigators to develop further strategies for achieving clinically-relevant ultra-stable bioelectronics.